Diphtheria, Tetanus, and Pertussis Immunity in Indian Adults and Immunogenicity of Td Vaccine - Kulkarni, Prasad S. (International Scholarly Research Network, 2011)
Rise of diphtheria cases in adults is a cause of concern worldwide. Pertussis is also now affecting adults. We assessed serum levels of tetanus, diphtheria and pertussis antibodies in 62 adults in Pune, India, who had missed their primary immunization. All adults were then given three doses of tetanus-diphtheria (Td) vaccine at 0, 1, and 6 months. All adults were immune to tetanus but 78% had long-term protection. For diphtheria, 88% were protected but only 9% had long term immunity. Only 60% were immune to pertussis. After three doses of the vaccine, long term immunity to both tetanus and diphtheria increased to 87% and 97%, respectively (P < 0.05). Geometric mean titres (GMT) of both antibodies also increased significantly. The vaccine caused minor local reactions and mild fever in a few subjects. There is need of three doses of Td vaccination in those Indian adults, who missed their primary immunization. Susceptibility to pertussis also needs to be further explored.